HE4 is superior to CA125 in the detection of recurrent disease in high-risk endometrial cancer patients - Karin Abbink; Petra LM Zusterzeel; Anneke J Geurts-Moespot; Antonius E van Herwaarden; Johanna MA Pijnenborg; Fred CGJ Sweep; Leon FAG Massuger (Tumor Biology, 2018)
Objective: To date, biomarkers are not routinely used in endometrial cancer diagnosis, prognosis, and follow-up. The purpose of this study was to evaluate whether serum HE4 was related to clinicopathological risk factors and outcome. Second, the role of serum HE4 and CA125 was assessed as indicator for recurrent disease during follow-up. Methods: A total of 174 patients with endometrial cancer between 1999 and 2009 were selected for this retrospective study. Serum HE4 and CA125 were analyzed at primary diagnosis, during follow-up, and at the time of recurrence. Correlations with clinicopathological factors were studied by univariate and multivariate survival analyses. Lead time was calculated in order to determine which serum marker was elevated prior to clinical detection of recurrent disease. Results: Serum levels of HE4 and CA125 were significantly associated with high tumor grade, myometrial invasion, lymph node involvement, and advanced stage (p < 0.01). HE4 was an independent prognostic factor for reduced disease-free survival and overall survival with hazard ratios of 2.96 (95% confidence interval: 1.18–7.99) and 3.27 (95% confidence interval: 1.18–9.02), respectively. At recurrence, 75% of the patients had an elevated HE4 compared to 54% with an elevated CA125. HE4 levels were more frequently elevated in patients with distant metastasis compared to local recurrences, 67% and 37%, respectively. Serum HE4 detected a recurrence with a median of 126 days earlier than clinical confirmation. Conclusion: Elevated serum HE4 is an independent risk factor for reduced disease-free survival and overall survival. HE4 seems to be superior to CA125 in the detection of recurrent disease during follow-up, mainly in high-risk endometrial cancer patients who are more prone to distant metastasis.